Helicobacter pylori eradication therapy in an area of southeastern Brazil: a cohort study - Silva, Alessandro Lisboa da; Batista, Rodrigo Siqueira; Miguel, Paulo Sérgio Balbino; Moreira, Tiago Ricardo; Gomes, Andreia Patrícia (Ciência e Natura, 2022)
The Second and Third Brazilian Consensuses on Helicobacter pylori indicate the combination of a proton pump inhibitor (PPI), amoxicillin, and clarithromycin as the first-line therapy for eradicating this pathogen, but this regimen has been criticized for the recent decrease in its efficacy in several parts of the world. There are little data on the efficacy of H. pylori eradication regimens in the interior of Brazil. OBJECTIVE: To describe the treatments prescribed for the eradication of H. pylori with their respective efficacy rates in a cohort living in the Zona da Mata of Minas Gerais. DESIGN: A retrospective cohort study with treatment-naïve patients known to have gastric infection by H. pylori, residents of the Zona da Mata of Minas Gerais, submitted to eradication therapy of this pathogen in the periods 2007 to 2011, and 2013 to 2016. The H. pylori eradication rates obtained with the prescribed treatments were evaluated as outcomes. RESULTS: We analyzed 5010 medical records from a single health service, with 264 prescriptions for initial treatments to eradicate H. pylori using PPI associated with amoxicillin and clarithromycin for 7 days in 243 cases (88.25%). The overall efficacy rate of this regimen was 54.07%, with no differences in efficacy between the two periods analyzed (2007 to 2011: 54.55%, 2013 to 2016: 53.65, p = 0.892) There were no differences in efficacy according to the choice of PPI: Omeprazole-AC7: 52.55%, OR = 1 (72 successes out of 137); Lansoprazole-AC7: 44.18%. OR = 1.399, p = 0.28 (38 out of 86); and Pantoprazole-AC-7: 60%, OR = 0.739, p = 0.701 (12 out of 20). CONCLUSIONS: In this cohort, the efficacy rates of the regimens recommended by the Brazilian Consensus on Helicobacter pylori were lower than those previously described in the Brazilian literature, suggesting the need for a revision of the official recommendations.